2016
DOI: 10.1109/mcom.2016.7452263
|View full text |Cite
|
Sign up to set email alerts
|

Aerial base stations with opportunistic links for next generation emergency communications

Abstract: Fast deployable and reliable mission-critical communication networks are fundamental requirements to guarantee the successful operations of public safety officers during disaster recovery and crisis management preparedness. The ABSOLUTE project focused on designing, prototyping and demonstrating a high-capacity IP mobile data network with low latency and large coverage suitable for many forms of multimedia delivery including public safety scenarios. The ABSOLUTE project combines aerial, terrestrial and satelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(21 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…Furthermore, a reduced dependency on intermediate communication with a centralized entity adds the potential of delivering very low average latency. Previous studies have found a fully centralized concept to limit robustness in disaster scenarios, motivating the implementation of eNB for use as aerial base stations with partial autonomy [7]. Some autonomous LTE base stations are commercially available but only operate in a limited number of frequency bands and their form factors still prohibit integration into UAV and sometimes even into cars.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a reduced dependency on intermediate communication with a centralized entity adds the potential of delivering very low average latency. Previous studies have found a fully centralized concept to limit robustness in disaster scenarios, motivating the implementation of eNB for use as aerial base stations with partial autonomy [7]. Some autonomous LTE base stations are commercially available but only operate in a limited number of frequency bands and their form factors still prohibit integration into UAV and sometimes even into cars.…”
Section: Introductionmentioning
confidence: 99%
“…Relaying operation has been standardized in release 10 of the LTE specification [8] while UAVs acting as relay stations have been extensively covered in [7] [9]. Although pre release 10 user equipment (UE) is compatible with relay nodes (RN), the standard only supports two-hop operation (via a single RN) and does not consider mobile RN [10].…”
Section: Introductionmentioning
confidence: 99%
“…Among the many applications, the use of UAVs for achieving high data-rate wireless communication is expected to play an essential role in future wireless systems. In fact, UAV-aided wireless communication becomes a promising solution to provide wireless connectivity for devices without infrastructure coverage [14]. There has been recent interest in utilizing aerial access points (AAPs) mounted on drones, which could be utilized for offering on-demand connectivity in cases of imminent network overload.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of the Temporal Counting Bloom Filter (TCFB) enables the encoding of contents and human interest as tags in the system to reduce terminal consumption and realize further real-world trace-driven simulations that ensure the efficiency of B-SUB under different network conditions [7] . Gomez et al [8] proposed the ABSOLUTE project and focused on designing, prototyping, and demonstrating a high-capacity IP mobile data network with low latency and extensive suitable for many forms of multimedia delivery in different settings, including public safety scenarios. Markakis et al [9] presented the EMYNOS project, for the design and implementation of a next-generation platform capable of accommodating rich-media emergency calls that combine voice, text, and video, thus providing a powerful tool for coordinating communication among citizens, call centers, and first responders.…”
Section: Introductionmentioning
confidence: 99%